Brightness preserving and contrast limited bi-histogram equalization for image enhancement - Zhijun Yao; Zhongyuan Lai; Chun Wang; Wu Xia (2016 3rd International Conference on Systems and Informatics (ICSAI), 2016)
In the paper, we propose a histogram equalization-based image enhancement method named Brightness Preserving and Contrast Limited Bi-histogram Equalization (BPCLBHE). Our method includes three steps: (i) First, we use the average intensity value of the image to divide the input original image into two sub-images. (ii) Second, the histogram clipping approach is used to control enhancement rate. (iii) Finally, we use the individual clipped histogram to equalize each sub image independently and then two enhanced sub images are stitched into an output image. From the simulation results, it can be concluded that BPCLBHE obtains the best enhancement effect compared to other methods, in terms of visual inspection and multiple image quality evaluation measures.